Bidirectional Mendelian randomization analysis investigating the genetic association between primary breast cancer and colorectal cancer - Liu, Yi; Si, Mingxuan; Qian, Yawei; Liu, Yang; Wang, Zichen; Zhang, Tongyu; Wang, Zhenhuan; Ye, Kun; Xiang, Cuijuan; Xu, Linlin; Zhang, Yanping; Xiao, Zhihan (Frontiers in Immunology, 2024)
With the advancement in early diagnosis and treatment, the prognosis for individuals diagnosed with breast cancer (BC) has improved significantly. The prognosis of primary breast cancer (PBC) survivors can be significantly influenced by the occurrence of colorectal cancer (CRC) as a secondary primary cancer (SPC). The objective of this study is to explore the possible genetic association between PBC and CRC, aiming to lay a groundwork for the development of preventive strategies against SPC-CRC following BC surgery.We employed a bidirectional two-sample Mendelian randomization (MR) approach to thoroughly examine genetic instrumental variables (IVs) derived from genome-wide association studies (GWAS) conducted on PBC and CRC. And applied inverse variance weighted (IVW) and multiple other MR methods (weighted median, simple median, MR-PRESSO and MR-RAPS) to evaluate the association between the two cancers (PBC and CRC) at genetic level. Furthermore, the robustness of the findings was further confirmed through the utilization of the genetic risk score (GRS) method in a secondary analysis.: Forward MR analysis, a total of 179 BC genetic IVs, 25 estrogen receptor-negative (ER-) genetic IVs and 135 ER-positive (ER+) genetic IVs were screened. Reverse MR analysis, 179 genetic IVs of CRC, 25 genetic IVs of colon cancer, 135 genetic IVs of rectal cancer, 25 genetic IVs of left colon cancer and 135 genetic IVs of right colon cancer were screened. IVWand other MR methods found no significant genetic association between PBC and CRC (P > 0.05). Subgroup analysis also showed that ER-BC and ER+ BC were not correlated with the occurrence of CRC (P > 0.05). The findings of the secondary analysis using GRS were cconsistent with those obtained from the primary analysis, thereby confirming the robustness and reliability of this study.Conclusions: Our findings do not provide any evidence supporting the association between PBC and CRC at the genetic level. Further large-scale prospective studies are warranted to replicate our findings.